Caracterização de um novo modelo de maturação de oócito in vitro e participação do mTOR na ovulação em bovinos - Rosa, Paulo Roberto Antunes da (2016)
In the first study, we characterized an in vitro culture system able to delaying meiosis resumption of bovine oocytes. Firstly, we demonstrated that the use of an EGFR inhibitor (AG1478; 5μM) in a culture system with follicular hemisections (FHS) was effective to maintain 89.3% of the oocytes in germinal vesicle stage (GV) during 15 h. This blocking effect was dependent on the FHS, since in its absence only 40% of the oocytes remain in GV stage. The meiosis blockage was totally reversible, since the oocytes reached matured stages after an additional 18 and 20 h maturation period and were able to support the embryonic development after in vitro fertilization. Regarding the molecular profile of the cells involved in the blocking system, we did not observe treatment effect on mRNA expression of the genes evaluated in oocyte. However, in cumulus cells, whereas the expression of EGR-1, TNFAIP6 and HAS2 was inhibited by AG1478 treatment, the expression of CX43 and IMPDH1 was decreased by FHS influence. Moreover, in the granulosa cells we observed a downregulation in the expression levels of PGR and ADAMTS1 by AG1478 treatment. The Western blot data revealed that the treatment with AG1478 plus FHS induces a downregulation in p-ERK1/2 protein abundance. In the next experiment, we verified that the AngII or PGE2 and PGF2α did not reverse the inhibitory effect of AG1478 plus FHS on meiosis resumption. In conclusion, findings from this study revealed an effective and reversible system to prevent meiosis resumption of bovine oocytes. In the second study, we investigate the role of mTOR system and its relation with LH regulated genes during preovulatory period in cattle. Using an in vivo model, we demonstrated mTOR kinase activity in granulosa cells 3 and 6 h after induction of ovulation with GnRH. In the similar moments (3 h after GnRH), we observed an increase in p-ERK1/2, STAR and EGR1 protein abundance. The inhibition of mTOR kinase activity by intrafollicular injection of rapamycin did not alter the ovulation rate. However, the treatment of granulosa cells in vitro with rapamycin interrupted the LH-induced increase in EREG mRNA levels. Moreover, the effect of rapamycin in culture was proved by inhibiting the p-P70S6K protein levels. In the same Western blot analysis, we verified that rapamycin may be inducing AKT activity and did not alter Phospho-ERK1/2 status and EGR1 protein abundance. These results provided the first evidence in cattle that mTOR system is upregulated by LH at time points similar to p-ERK1/2, STAR and EGR1. In addition, the mTOR inhibition data contribute to suggest an AKT dependent pathway during ovulation process, in which occurs ERK1/2 activation in a pathway independent of EREG, AREG and PTGS2 mRNA levels.